Information Manipulation Through a Linguistic Anthropological Lens (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2025)
This project analyzes the phenomenon of information manipulation through a linguistic anthropological lens, exploring how misinformation, malinformation, and disinformation permeate modern-day media. Analyzing misinformation during COVID-19, malinformation during political campaigns, and disinformation pushed by corporations, this writing piece showcases the role of framing and discourse in spreading manipulative information across these various cases. Following the analysis, the paper offers practical insights on navigating complex media landscapes using frameworks of linguistic anthropology.For additional context, listen to the author's reflection on the piece below.